(untitled) (Arquivos do Mudi, 2026)
Objectives: To provide an integrative overview of studies addressing the sustainable development of soybean cultivation in Brazil, with an emphasis on the principal entomopathogenic fungi employed in the phytosanitary management of insect pests. Methods: A systematic literature review was conducted on insect pests associated with soybean and the fungal bioinsecticide market, analyzing the biological characteristics of microorganisms based on data retrieved from multiple scientific databases and publications spanning 2015 to 2025. Results: The major soybean pests belong predominantly to the families Noctuidae and Pentatomidae. Biological control through fungal bioinsecticides - mainly formulations of Beauveria bassiana, Cordyceps fumosorosea, and Metarhizium anisopliae - represents approximately 69% of the Brazilian microbial bioinsecticide market. Conclusion: The sustainable management of soybean pests in Brazil using fungal formulations has demonstrated high efficiency. However, the implementation of an integrated and adaptive management framework, supported by consistent public policies is crucial to ensure sustainable production.